Method for preparing super-hydrophobic anti-freezing coating by using waste wind turbine blade

By grinding and chemical modification of the scrap wind power blade materials, high-performance superhydrophobic antifreeze coatings are prepared, which solves the problem of recycling and utilization of waste wind power blades and realizes efficient reuse and high-value applications.

CN119490792AActive Publication Date: 2025-02-21TIANFU YONGXING LAB

Patent Information

Application Number
CN202411694553.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-21
Estimated Expiration
2044-11-25

AI Technical Summary

Technical Problem

The recycling of waste wind power blades has huge challenges, especially the three-dimensional cross-linking network of epoxy resins makes it difficult to remodel and dissolve, making recycling difficult, and existing recycling methods such as incineration and landfill can lead to environmental pollution.

Method used

By grinding waste wind power blade materials with special properties by using a grinding disc-shaped solid-phase chemical reactor, wind power blade powders with special properties were prepared, and thiol-ene click chemical reaction of fluorine-containing acrylates were generated to produce super- The hydrophobic antifreeze composite powder is finally prepared to produce high-performance superhydrophobic antifreeze coatings.

Benefits of technology

The efficient reuse of waste wind power blades has been achieved. The super-hydrophobic antifreeze coating prepared has a layered structure, low surface free energy, good mechanical properties, durability, chemical stability and ice resistance, which expands the materials of waste wind power blades. High-value application scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119490792A_ABST
    Figure CN119490792A_ABST
Patent Text Reader

Abstract

The invention provides a method for preparing a super-hydrophobic anti-freezing coating by utilizing a waste wind power blade, which comprises the following steps of: primarily crushing a waste wind power blade material, adding into a millstone-shaped solid-phase mechanochemical reactor for grinding and crushing, collecting to obtain wind power blade powder, and modifying the wind power blade powder by a sulfydryl-containing silane coupling agent to obtain the super-hydrophobic anti-freezing coating. And carrying out a thiol-ene click chemical reaction with fluorine-containing acrylate to generate super-hydrophobic anti-freezing composite powder, and mixing the super-hydrophobic anti-freezing composite powder with a solvent to prepare the super-hydrophobic anti-freezing coating. The high-performance super-hydrophobic anti-freezing coating is prepared by modifying wind power blade powder with special performance obtained by grinding a waste wind power blade material based on an industrial millstone-shaped solid-phase mechanochemical reactor, and a coating layer formed by coating the coating has the characteristics of a hierarchical structure and low surface free energy; and good mechanical performance, durability, chemical stability and anti-icing performance are achieved, and a high-value application scene is expanded for recycling of waste wind power blade materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of high-value reuse of discarded / retired wind turbine blade materials and hydrophobic coatings, and specifically relates to a method for preparing super-hydrophobic antifreeze coatings using discarded wind turbine blades, and particularly to using an industrial grinding disc-shaped solid phase force chemical reactor disclosed in Chinese invention patent CN114534660B to process the above-mentioned discarded wind turbine blade materials. Background Art

[0002] As the global demand for renewable energy increases, wind energy is increasingly becoming part of the global energy landscape due to its sustainability and continued availability. However, a wave of wind turbine (WT) blade retirements is imminent as obsolete wind turbine components are replaced and installed equipment reaches the end of their useful life (typically 20 to 25 years), leading to significant challenges associated with composite waste management. WT blades are primarily composed of glass fiber or carbon fiber reinforced epoxy resin (GFRP / CFRP), and the three-dimensional cross-linked network of discarded epoxy resin makes it difficult to reshape and dissolve, posing a huge challenge for recycling. In fact, epoxy recycling is generally considered unfeasible. Current estimates indicate that approximately 2 million tons of wind blades will be generated each year, and it is expected that 43 million tons of wind blades will be discarded worldwide by 2050, which will raise serious environmental concerns. Currently, the main methods for managing waste blades on a large scale still focus on incineration and landfilling, both of which seriously pollute the environment and waste precious resources. At the same time, the unsustainability of these methods conflicts with the principles of circular economy and carbon neutrality. Therefore, there is an urgent need to develop innovative recycling modes for WT blades that are consistent with reducing environmental impact and promoting resource reuse. To address these challenges, several new recycling methods have been proposed in recent years to address the recycling challenges of thermoset composites in sustainable energy infrastructure. These methods include mechanical recycling techniques (e.g., milling, pulverizing, and crushing), chemical processes (e.g., hydrolysis, glycolysis, and dissolution), and thermal treatments (e.g., pyrolysis, thermolysis, and fluidization processes).

[0003] However, these methods have serious limitations, such as the high requirements for infrastructure, energy consumption and cost of pyrolysis. Therefore, from the perspective of environment and resource utilization, it is still a challenge to achieve green, efficient and value-added recycling of epoxy thermoset composites. Among these recycling methods, mechanical recycling is considered to be an efficient and large-scale application method, but recycling by this method will cause glass fiber breakage and reduce the aspect ratio. At present, WT blade waste recycled by mechanical means is generally used as low value-added fillers, such as building materials, concrete fillers, and bulk molding compounds.

[0004] In order to provide a new way for the recycling of discarded wind turbine blades, the inventors provided a method for preparing highly compatible and reactive fillers using discarded wind turbine blades in the prior patent application "Glass fiber reinforced plastic recycled products using discarded wind turbine blades as raw materials and preparation method thereof" (CN118063854A), which comprises adding the discarded wind turbine blade products into a grinding disc-shaped solid phase force chemical reactor after pretreatment for grinding and crushing to obtain ultrafine wind turbine blade powder, and then mixing the ultrafine wind turbine blade powder with an activator and co-grinding to obtain a highly compatible and reactive filler; and then using the highly compatible and reactive filler as part of the raw material to prepare the glass fiber reinforced plastic recycled products.

[0005] However, in the above patent application, although a new basic approach is provided for the recycling of discarded wind turbine blades, the highly compatible and reactive fillers prepared by the invention can be added to resin base materials as part of the raw materials, that is, they have basic enhanced functionality, and a new recycling approach for discarded wind turbine blades is successfully pointed out. However, in the technical solution of the patent application, there is still a blank in terms of high-value empowerment for the reuse of discarded wind turbine blades. Summary of the invention

[0006] In order to solve the problems in the above-mentioned prior art, the present invention provides a method for preparing a super-hydrophobic antifreeze coating using discarded wind turbine blades. The wind turbine blade powder with special properties is obtained by grinding the discarded wind turbine blade materials in an industrial grinding disc-shaped solid-phase force chemical reactor, and a high-performance super-hydrophobic antifreeze coating is prepared after modification. The coating formed by coating has the characteristics of a hierarchical structure and low surface free energy, as well as good mechanical properties, durability, chemical stability and anti-icing properties, which expands high-value application scenarios for the reuse of discarded wind turbine blade materials.

[0007] To achieve the above objectives, the present invention is implemented by adopting a technical solution consisting of the following technical measures.

[0008] In one aspect, the present invention provides a method for preparing a super-hydrophobic antifreeze coating using discarded wind turbine blades, which mainly comprises the following steps:

[0009] (1) After pretreatment including cleaning, the waste wind turbine blade materials are crushed into wind turbine blade fragments with an average particle size of no more than 3 cm;

[0010] (2) adding the wind turbine blade fragments obtained in step (1) into a grinding disc-shaped solid phase force chemical reactor for grinding and pulverization, and collecting the wind turbine blade powder after the grinding is completed; wherein the process parameters of the grinding disc-shaped solid phase force chemical reactor are: grinding pressure of 4 to 6 MPa, the grinding disc surface temperature is controlled at 20 to 30° C. by passing a circulating cooling liquid, the grinding number is at least 1, and the grinding disc speed is 20 to 40 rpm;

[0011] (3) modifying the wind turbine blade powder obtained in step (2) with a silane coupling agent containing a mercapto group to obtain a mercapto-functionalized modified wind turbine blade powder;

[0012] (4) subjecting the thiol-functionalized modified wind turbine blade powder obtained in step (3) to a fluorinated acrylate through a thiol-ene click chemical reaction to generate a super-hydrophobic antifreeze composite powder;

[0013] Wherein, the number of fluorine atoms in the fluorine-containing acrylate is at least 1 and the carbon chain length is 4 to 20;

[0014] (5) According to the mass fraction, the super hydrophobic antifreeze composite powder obtained in step (4) is used as a raw material, and is mixed evenly with the following other raw materials to prepare a super hydrophobic antifreeze coating:

[0015] 3-5 parts of super hydrophobic antifreeze composite powder,

[0016] 90-95 parts of solvent.

[0017] In this article, step (1) includes a pretreatment of cleaning, which is mainly to remove impurities on the surface of the waste wind turbine blade material. If necessary, part of the non-wind turbine blade material needs to be removed. Technical personnel in this field can perform specific treatment according to the actual conditions of the waste wind turbine blade products that need to be recycled and based on the existing technology.

[0018] In this article, the wind turbine blade fragments processed and crushed to an average particle size of no more than 3 cm in step (1) can be processed and crushed in a conventional manner to facilitate the placement of the fragments into a disc-shaped solid phase force chemical reactor for grinding, for example, by using existing conventional crushing equipment such as a jaw crusher, a planetary ball mill, and a cryogenic ball mill.

[0019] The millstone-shaped solid phase force chemical reactor in step (2) is an industrial millstone-shaped solid phase force chemical reactor disclosed in Chinese invention patent CN114534660B.

[0020] It should be noted that the industrial grinding disc-shaped solid-phase force chemical reactor is based on the principle of the force chemical reactor disclosed in the prior authorized patent ZL95111258.9, and is an industrial equipment that was finally improved and launched. It is significantly different from the structure of the laboratory prototype when ZL95111258.9 was applied for. A new grinding disc structure is designed for industrial high-efficiency force chemical grinding treatment. The vertical setting of the grinding disc in the past is improved to a horizontal setting, and the size of the grinding disc is greatly increased. Based on the horizontal setting and large size of the grinding disc, the relevant fixed grinding disc assembly and hydraulic lifting system are innovatively designed, which greatly improves its three-dimensional shear force, thereby having industrial mass production efficiency.

[0021] Usually, the grinding times are at least 1 time. When the grinding times are 2 times or more, the actual process operation is to grind the material through a disc-shaped solid phase force chemical reactor, collect the product at the discharge end and then place it in a disc-shaped solid phase force chemical reactor for grinding again. The above process is regarded as grinding twice.

[0022] Herein, the temperature of the grinding disc surface in step (2) is controlled to be 20-30° C. by introducing circulating cooling liquid, and the cooling liquid is water, ethylene glycol or glycerol.

[0023] Herein, the mercapto-containing silane coupling agent in step (3) is a commercially available silane coupling agent containing mercapto functional groups commonly used in the prior art, for example, any one or more of KH590 and KH580.

[0024] In this article, the wind turbine blade powder described in step (3) is modified by a thiol-containing silane coupling agent to prepare a thiol-functionalized modified wind turbine blade powder, wherein the material is modified by a thiol-containing silane coupling agent, which is a conventional modification method in the art, and its specific modification conditions and operations can all refer to the instructions for use of the above-mentioned specifically selected silane coupling agent or the records in the prior art literature. Usually, in the modification process, the thiol-containing silane coupling agent needs to be diluted to a coupling agent solution with a mass concentration of 1 to 3wt%, and then the wind turbine blade powder is added to react; or the wind turbine blade powder is fully diluted and dispersed to a mixed solution A with a mass concentration of 1 to 3wt%, and then the thiol-containing silane coupling agent is added to react; wherein the dilution and the solvent used for dilution are selected according to the conventional known method when the silane coupling agent is used, and those skilled in the art can directly select an appropriate method according to the common knowledge in the art or according to the instructions for use of the thiol-containing silane coupling agent.

[0025] In order to better illustrate the present invention and provide a technical solution for reference, the wind turbine blade powder described in step (3) is modified by a silane coupling agent containing a mercapto group to obtain a mercapto-functionalized modified wind turbine blade powder, and the specific method is as follows:

[0026] By weight, 1 to 2 parts of wind turbine blade powder are added to 90 to 99 parts of ethanol and 1 to 3 parts of deionized water, and the mixture is dispersed by stirring for 30 to 40 minutes. Then, 1 to 5 parts of a mercapto-containing silane coupling agent are added, and the mixture is stirred and reacted at a temperature of 90 to 100° C. for 8 to 16 hours. After the time is up, the mercapto-functionalized modified wind turbine blade powder is obtained by filtering, washing and drying.

[0027] In one technical solution, the fluorinated acrylate in step (4) includes 1H,1H,2H,2H-perfluorodecyl acrylate, trifluoroethyl acrylate, N-ethyl perfluorooctylsulfonamidoethyl acrylate, 1,1,2,2-tetrahydroperfluorohexyl methacrylate, 1,1,2,2-tetrahydroperfluorodecyl methacrylate, 1,1,2,2-tetrahydroperfluorooctyl methacrylate, 1,1,2,2-tetrahydroperfluorododecyl methacrylate, 1,1,1,3,3,3-hexafluoroisopropyl acrylate, 3-( Any one of perfluoro-5-methylhexyl)-2-hydroxypropyl methacrylate, 1H,1H,2H,2H-perfluorooctanol acrylate, 1,1,2,2-tetrahydroperfluorotetradecane acrylate, 2,2,3,3-tetrafluoropropyl methacrylate, 1H,1H-perfluoropropyl methacrylate, 2-(perfluorobutyl)ethyl acrylate, perfluoroalkylethyl methacrylate, perfluoroalkylethyl acrylate, nonafluorohexadecyl acrylate, (2H-perfluoropropyl)-2-acrylate, and (perfluorocyclohexyl) methacrylate.

[0028] In this article, the thiol-functionalized modified wind turbine blade powder and the fluorinated acrylate in step (4) are reacted by a thiol-ene click chemistry reaction to generate a super hydrophobic antifreeze composite powder. Those skilled in the art can select the thiol-functionalized modified wind turbine blade powder and the fluorinated acrylate provided by the present invention, and know the reaction conditions and process operations of the thiol (thiol-ene click chemistry) reaction according to the common knowledge of chemical synthesis in the field. For example, the initiator, solvent and reaction target product used therein can refer to the conventional thiol (thiol-ene click chemistry) reaction.

[0029] In order to better illustrate the present invention and provide a technical solution for reference, the thiol-functionalized modified wind turbine blade powder and the fluorinated acrylate in step (4) are subjected to a thiol-ene click chemical reaction to generate a super hydrophobic antifreeze composite powder, wherein the thiol-functionalized modified wind turbine blade powder is fully diluted and dispersed into a mixed solution B with a mass concentration of 1 to 10 wt%, the fluorinated acrylate is diluted to a fluorinated acrylate solution with a mass concentration of 2 to 25 wt%, the fluorinated acrylate solution is added to the mixed solution B under stirring, and then an initiator is added, and the reaction is stirred at a temperature of 60 to 80° C. for 9 to 12 hours. After the time is up, the super hydrophobic antifreeze composite powder is obtained by filtering, washing and drying.

[0030] In the above technical solution, the initiator is an initiator commonly used in the polymerization reaction in the technical field, and the technicians in the technical field can select a suitable initiator according to actual needs. For example, the initiator includes any one of azobisisobutyronitrile, triethylamine, 2-methyl-1-(4-methylthiophenyl)-2-morpholinyl-1-propanone and 4-dimethylaminopyridine; the addition amount of the initiator is 1 to 20% of the mass of the thiol functionalized modified wind turbine blade powder.

[0031] In this article, the solvent in step (5) is selected from solvents commonly used in chemical coating products, such as any one or more of anhydrous ethanol, n-hexane, cyclohexane, dichloromethane, n-heptane, n-octane, acetone, benzene, toluene, and ethyl acetate.

[0032] In one preferred technical solution, the super hydrophobic antifreeze coating further comprises, by weight, the following raw materials:

[0033] 1 to 10 parts of filler,

[0034] 1 to 10 parts of additives.

[0035] Among them, in order to improve the physical strength of the coating after the super hydrophobic antifreeze coating is used, the raw material components include a filler, and the filler is a well-known inorganic or organic filler, preferably one or more of titanium dioxide, bentonite, barium sulfate, spherical silica, nano-calcium carbonate, and talc. Furthermore, it is preferred that well-known and commonly used metal oxides are used as both fillers and pigments.

[0036] Wherein, the additive is one or more combinations of pigment, tackifier, defoamer, leveling agent, antioxidant and rust inhibitor. Generally, the above-mentioned pigment, tackifier, defoamer, leveling agent, antioxidant and rust inhibitor are well-known and commonly used.

[0037] It should be noted that the super hydrophobic antifreeze coating provided by the present invention follows the conventional coating method of hydrophobic coating in the chemical industry. For example, after a layer of adhesive is applied to a substrate with a smooth surface, the super hydrophobic antifreeze coating is applied to the surface, and the super hydrophobic antifreeze coating is obtained after drying.

[0038] Typically, the coating method is one of spraying, brushing, and dipping; the adhesive includes but is not limited to 3M adhesive, common coating resin adhesive, inorganic adhesive, etc.; the substrate base material is any one of textiles, glass, wood, stainless steel mesh, copper mesh, sponge, aluminum, iron, cement board, ceramics or paper products.

[0039] The present invention has the following beneficial effects:

[0040] (1) The present invention provides a method for preparing a super-hydrophobic antifreeze coating using discarded wind turbine blades, based on a wind turbine blade powder with special properties obtained by grinding discarded wind turbine blade materials in an industrial disc-shaped solid-phase force chemical reactor. Comparative experiments have shown that the powder ground in an industrial disc-shaped solid-phase force chemical reactor has significantly improved hydrophobic properties under similar particle size conditions compared to powders obtained by other crushing / crushing methods. The coating formed by using the powder to prepare the coating has a rough surface and a multi-scale structure, and this structural characteristic is combined with subsequent hydrophobic modification to improve the hydrophobicity, thereby achieving efficient expression of the modification effect.

[0041] (2) The present invention provides a method for preparing a super-hydrophobic antifreeze coating using discarded wind turbine blades, wherein thiol-functionalized modified wind turbine blade powder and fluorinated acrylate are reacted via thiol (thiol-ene click chemistry) to generate a super-hydrophobic antifreeze composite powder, which exhibits excellent hydrophobic properties. The coating prepared by the coating has the characteristics of a hierarchical structure and low surface free energy, as well as good mechanical properties, durability, chemical stability and anti-icing properties, and also has excellent stain resistance and self-cleaning properties, thereby expanding high-value application scenarios for the reuse of discarded wind turbine blade materials.

[0042] (3) The present invention provides a method for preparing a super-hydrophobic antifreeze coating using discarded wind turbine blades. The coating formed by coating the coating prepared by the present invention reduces heat transfer and improves anti-freeze ability by utilizing its multi-scale rough surface structure, thereby increasing the functional application of recycled materials. This not only challenges the traditional concept that mechanically recycled wind turbine blades can only be used as low-value fillers, but also demonstrates the huge potential for value-added recycling of glass fiber reinforced polymers. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 The SEM image of the wind turbine blade powder prepared in Example 1 is used to verify the present invention.

[0044] Figure 2It is a schematic diagram of the reaction process of steps (2) to (4) in Example 3 of the present invention and the FTIR spectrum, XPS spectrum, high-resolution carbon spectrum, SEM image, mapping image and TG curve diagram of the intermediate product. Among them, Figure (a) is a schematic diagram of the reaction process of steps (2) to (4) in Example 3; Figure (b) is a FTIR comparison spectrum of the wind turbine blade powder (WGE) obtained in step (2) of Example 3, the thiol functionalized modified wind turbine blade powder (WGE@KH590) obtained in step (3), and the super hydrophobic antifreeze composite powder (S@WGE@KH590) obtained in step (4); Figure (c) is the wind turbine blade powder (WGE) obtained in step (2) of Example 3, the thiol functionalized modified wind turbine blade powder (WGE@Kh) obtained in step (3), and the super hydrophobic antifreeze composite powder (S@WGE@Kh) obtained in step (4) XPS comparison spectrum; Figure (d) is the high-resolution carbon spectrum of the thiol functionalized modified wind turbine blade powder obtained in step (3) of Example 3; Figure (e) is the high-resolution carbon spectrum of the super-hydrophobic antifreeze composite powder obtained in step (4) of Example 3; Figure (f) is the SEM image and mapping image of the super-hydrophobic antifreeze composite powder obtained in step (4) of Example 3; Figure (g) is the TG curve comparison diagram of the wind turbine blade powder (WGE) obtained in step (2) of Example 3, the thiol functionalized modified wind turbine blade powder (WGE@Kh) obtained in step (3), and the super-hydrophobic antifreeze composite powder (S@WGE@Kh) obtained in step (4).

[0045] Figure 3 This is a SEM image of the surface of the coating sample in Example 3 of the present invention. DETAILED DESCRIPTION

[0046] In order to further understand the present invention, the preferred embodiments of the present invention are described below in conjunction with examples, but it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the invention. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve it. It is particularly important to point out that all similar substitutions and modifications are obvious to those skilled in the art, and they are all considered to be included in the present invention. The methods and applications of the present invention have been described through preferred embodiments, and relevant personnel can obviously change or appropriately change and combine the methods and applications described herein without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention. Although it is believed that those of ordinary skill in the art fully understand the following terms, the following definitions are still stated to help illustrate the subject matter disclosed by the present invention.

[0047] In one aspect, the present invention provides a method for preparing a super-hydrophobic antifreeze coating using discarded wind turbine blades, which mainly comprises the following steps:

[0048] (1) After pretreatment including cleaning, the waste wind turbine blade materials are crushed into wind turbine blade fragments with an average particle size of no more than 3 cm;

[0049] (2) adding the wind turbine blade fragments obtained in step (1) into a grinding disc-shaped solid phase force chemical reactor for grinding and pulverization, and collecting the wind turbine blade powder after the grinding is completed; wherein the process parameters of the grinding disc-shaped solid phase force chemical reactor are: grinding pressure of 4 to 6 MPa, the grinding disc surface temperature is controlled at 20 to 30° C. by passing a circulating cooling liquid, the grinding number is at least 1, and the grinding disc speed is 20 to 40 rpm;

[0050] (3) modifying the wind turbine blade powder obtained in step (2) with a silane coupling agent containing a mercapto group to obtain a mercapto-functionalized modified wind turbine blade powder;

[0051] (4) subjecting the thiol-functionalized modified wind turbine blade powder obtained in step (3) to a fluorinated acrylate through a thiol-ene click chemical reaction to generate a super-hydrophobic antifreeze composite powder;

[0052] Wherein, the number of fluorine atoms in the fluorine-containing acrylate is at least 1 and the carbon chain length is 4 to 20;

[0053] (5) According to the mass fraction, the super hydrophobic antifreeze composite powder obtained in step (4) is used as a raw material, and is mixed evenly with the following other raw materials to prepare a super hydrophobic antifreeze coating:

[0054] 3-5 parts of super hydrophobic antifreeze composite powder,

[0055] 90-95 parts of solvent.

[0056] In this article, step (1) includes a pretreatment of cleaning, which is mainly to remove impurities on the surface of the waste wind turbine blade material. If necessary, part of the non-wind turbine blade material needs to be removed. Technical personnel in this field can perform specific treatment according to the actual conditions of the waste wind turbine blade products that need to be recycled and based on the existing technology.

[0057] In this article, the wind turbine blade fragments processed and crushed to an average particle size of no more than 3 cm in step (1) can be processed and crushed in a conventional manner to facilitate the placement of the fragments into a disc-shaped solid phase force chemical reactor for grinding, for example, by using existing conventional crushing equipment such as a jaw crusher, a planetary ball mill, and a cryogenic ball mill.

[0058] The millstone-shaped solid phase force chemical reactor in step (2) is an industrial millstone-shaped solid phase force chemical reactor disclosed in Chinese invention patent CN114534660B.

[0059] It should be noted that the industrial grinding disc-shaped solid-phase force chemical reactor is based on the principle of the force chemical reactor disclosed in the prior authorized patent ZL95111258.9, and is an industrial equipment that was finally improved and launched. It is significantly different from the structure of the laboratory prototype when ZL95111258.9 was applied for. A new grinding disc structure is designed for industrial high-efficiency force chemical grinding treatment. The vertical setting of the grinding disc in the past is improved to a horizontal setting, and the size of the grinding disc is greatly increased. Based on the horizontal setting and large size of the grinding disc, the relevant fixed grinding disc assembly and hydraulic lifting system are innovatively designed, which greatly improves its three-dimensional shear force, thereby having industrial mass production efficiency.

[0060] Usually, the grinding times are at least 1 time. When the grinding times are 2 times or more, the actual process operation is to grind the material through a disc-shaped solid phase force chemical reactor, collect the product at the discharge end and then place it in a disc-shaped solid phase force chemical reactor for grinding again. The above process is regarded as grinding twice.

[0061] Herein, the temperature of the grinding disc surface in step (2) is controlled to be 20-30° C. by introducing circulating cooling liquid, and the cooling liquid is water, ethylene glycol or glycerol.

[0062] Herein, the mercapto-containing silane coupling agent in step (3) is a commercially available silane coupling agent containing mercapto functional groups commonly used in the prior art. In one embodiment, for example, any one or more of KH590 and KH580 are selected.

[0063] In this article, the wind turbine blade powder described in step (3) is modified by a thiol-containing silane coupling agent to prepare a thiol-functionalized modified wind turbine blade powder, wherein the material is modified by a thiol-containing silane coupling agent, which is a conventional modification method in the art, and its specific modification conditions and operations can refer to the instructions for use of the above-mentioned specifically selected silane coupling agent or the records in the prior art literature. In one embodiment, during the modification process, the thiol-containing silane coupling agent needs to be diluted to a coupling agent solution with a mass concentration of 1 to 3wt%, and then the wind turbine blade powder is added to react; or the wind turbine blade powder is fully diluted and dispersed to a mixed solution A with a mass concentration of 1 to 3wt%, and then the thiol-containing silane coupling agent is added to react; wherein the dilution and the solvent used for dilution are selected according to the conventional known method when the silane coupling agent is used, and those skilled in the art can directly select an appropriate method according to the common knowledge in the art or the instructions for use of the thiol-containing silane coupling agent.

[0064] In order to better illustrate the present invention and provide an implementation method for reference, the wind turbine blade powder described in step (3) is modified by a silane coupling agent containing a mercapto group to obtain a mercapto-functionalized modified wind turbine blade powder, and the specific method is as follows:

[0065] By weight, 1 to 2 parts of wind turbine blade powder are added to 90 to 99 parts of ethanol and 1 to 3 parts of deionized water, and the mixture is dispersed by stirring for 30 to 40 minutes. Then, 1 to 5 parts of a mercapto-containing silane coupling agent are added, and the mixture is stirred and reacted at a temperature of 90 to 100° C. for 8 to 16 hours. After the time is up, the mercapto-functionalized modified wind turbine blade powder is obtained by filtering, washing and drying.

[0066] In one embodiment, the fluorinated acrylate in step (4) includes 1H, 1H, 2H, 2H-perfluorodecyl acrylate, trifluoroethyl acrylate, N-ethyl perfluorooctylsulfonamidoethyl acrylate, 1,1,2,2-tetrahydroperfluorohexyl methacrylate, 1,1,2,2-tetrahydroperfluorodecyl methacrylate, 1,1,2,2-tetrahydroperfluorooctyl methacrylate, 1,1,2,2-tetrahydroperfluorododecyl methacrylate, 1,1,1,3,3,3-hexafluoroisopropyl acrylate, 3-( Any one of perfluoro-5-methylhexyl)-2-hydroxypropyl methacrylate, 1H,1H,2H,2H-perfluorooctanol acrylate, 1,1,2,2-tetrahydroperfluorotetradecane acrylate, 2,2,3,3-tetrafluoropropyl methacrylate, 1H,1H-perfluoropropyl methacrylate, 2-(perfluorobutyl)ethyl acrylate, perfluoroalkylethyl methacrylate, perfluoroalkylethyl acrylate, nonafluorohexadecyl acrylate, (2H-perfluoropropyl)-2-acrylate, and (perfluorocyclohexyl) methacrylate.

[0067] In this article, the thiol-functionalized modified wind turbine blade powder and the fluorinated acrylate in step (4) are reacted by a thiol-ene click chemistry reaction to generate a super hydrophobic antifreeze composite powder. Those skilled in the art can select the thiol-functionalized modified wind turbine blade powder and the fluorinated acrylate provided by the present invention, and know the reaction conditions and process operations of the thiol (thiol-ene click chemistry) reaction according to the common knowledge of chemical synthesis in the field. For example, the initiator, solvent and reaction target product used therein can refer to the conventional thiol (thiol-ene click chemistry) reaction.

[0068] In order to better illustrate the present invention and provide an implementation method for reference, the thiol-functionalized modified wind turbine blade powder and the fluorinated acrylate in step (4) are subjected to a thiol-ene click chemical reaction to generate a super hydrophobic antifreeze composite powder, wherein the thiol-functionalized modified wind turbine blade powder is fully diluted and dispersed into a mixed solution B with a mass concentration of 1 to 10 wt%, the fluorinated acrylate is diluted to a fluorinated acrylate solution with a mass concentration of 2 to 25 wt%, the fluorinated acrylate solution is added to the mixed solution B under stirring, and then an initiator is added, and the reaction is stirred at a temperature of 60 to 80° C. for 9 to 12 hours. After the time is up, the super hydrophobic antifreeze composite powder is obtained by filtering, washing and drying.

[0069] In the above embodiment, the initiator is an initiator commonly used in the polymerization reaction in the technical field, and the technicians in the technical field can select a suitable initiator according to actual needs. For example, the initiator selection includes any one of azobisisobutyronitrile, triethylamine, 2-methyl-1-(4-methylthiophenyl)-2-morpholinyl-1-propanone and 4-dimethylaminopyridine; the addition amount of the initiator is 1-20% of the mass of the thiol functionalized modified wind turbine blade powder, such as 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20% or any range or point value therebetween.

[0070] In this article, the solvent in step (5) is selected from solvents commonly used in chemical coating products, and in one embodiment, for example, any one or more of anhydrous ethanol, n-hexane, cyclohexane, dichloromethane, n-heptane, n-octane, acetone, benzene, toluene, and ethyl acetate.

[0071] In one preferred embodiment, the super hydrophobic antifreeze coating further comprises, by weight, the following raw materials:

[0072] 1 to 10 parts of filler,

[0073] 1 to 10 parts of additives.

[0074] Among them, in order to improve the physical strength of the coating after the super hydrophobic antifreeze coating is used, the raw material components include a filler, and the filler is a well-known inorganic or organic filler, preferably one or more of titanium dioxide, bentonite, barium sulfate, spherical silica, nano-calcium carbonate, and talc. Furthermore, it is preferred that well-known and commonly used metal oxides are used as both fillers and pigments.

[0075] Wherein, the additive is one or more combinations of pigment, tackifier, defoamer, leveling agent, antioxidant and rust inhibitor. Generally, the above-mentioned pigment, tackifier, defoamer, leveling agent, antioxidant and rust inhibitor are well-known and commonly used.

[0076] It should be noted that the super hydrophobic antifreeze coating provided by the present invention follows the conventional coating method of hydrophobic coating in the chemical industry. For example, after a layer of adhesive is applied to a substrate with a smooth surface, the super hydrophobic antifreeze coating is applied to the surface, and the super hydrophobic antifreeze coating is obtained after drying.

[0077] Typically, the coating method is one of spraying, brushing, and dipping; the adhesive includes but is not limited to 3M adhesive, common coating resin adhesive, inorganic adhesive, etc.; the substrate base material is any one of textiles, glass, wood, stainless steel mesh, copper mesh, sponge, aluminum, iron, cement board, ceramics or paper products.

[0078] The present invention will be further explained in detail with reference to the following examples. However, it should be understood by those skilled in the art that these examples are provided for illustrative purposes only and are not intended to limit the present invention.

[0079] Example

[0080] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. The specific conditions not specified in the examples are carried out according to the conditions recommended by normal conditions or manufacturers. The reagents used or the instruments not specified by the manufacturer are all conventional products that can be obtained commercially. The application should not be construed as being limited to the specific examples described.

[0081] 1. Raw materials

[0082] Abandoned wind turbine blades, provided by Tianjin Longjin Energy Saving Technology Co., Ltd.;

[0083] Epoxy resin (EP-128), Chengdu Kemite Technology Co., Ltd.;

[0084] 1H,1H,2H,2H-Perfluorodecyl acrylate, 2,2′-azobis(2-methylpropionitrile) (AIBN), 4,4′-diaminodiphenylmethane (DDM), (3-mercaptopropyl)trimethoxysilane (KH-590), tetrahydrofuran (THF, anhydrous), Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0085] Ethanol (EtOH, AR), acetone (99.5%), hydrochloric acid (HCl, 36-38%), sodium hydroxide (NaOH, 96%) and deionized water were obtained from Chengdu Kelon Reagent Factory.

[0086] 2. Preparation method

[0087] (1) After pre-treatment including washing, the waste wind turbine blade materials are crushed into wind turbine blade fragments by a crusher;

[0088] (2) adding the wind turbine blade fragments obtained in step (1) into a grinding disc-shaped solid phase force chemical reactor for grinding and pulverization, and collecting the wind turbine blade powder after the grinding is completed; wherein the process parameters of the grinding disc-shaped solid phase force chemical reactor are: grinding pressure of 5 MPa, the grinding disc surface temperature is controlled at 20° C. by passing a circulating cooling liquid, the grinding number is at least 1, and the grinding disc speed is 40 rpm;

[0089] (3) Add 2 parts of the wind turbine blade powder obtained in step (2) to 96 parts of ethanol and 2 parts of deionized water, stirring for 30 minutes to disperse, then add 2 parts of KH590, stir and react at 100° C. for 12 hours, and after the time is up, filter, wash and dry to obtain thiol-functionalized modified wind turbine blade powder;

[0090] (4) Dispersing 5 parts of the thiol-functionalized modified wind turbine blade powder obtained in step (3) in 80 parts of THF as a mixed solution B, dissolving 5 parts of 1H,1H,2H,2H-perfluorodecyl acrylate in 40 parts of THF as a fluorine-containing acrylate solution, adding the fluorine-containing acrylate solution to the mixed solution B under stirring, and then adding 1 part of initiator AIBN, stirring and reacting at 80° C. for 12 hours. After the time is up, filtering, washing and drying to obtain a super hydrophobic antifreeze composite powder;

[0091] (5) According to the mass fraction, the super hydrophobic antifreeze composite powder obtained in step (4) is used as a raw material, and is mixed evenly with the following other raw materials to prepare a super hydrophobic antifreeze coating:

[0092] 3 parts of super hydrophobic antifreeze composite powder,

[0093] Ethanol 95 parts.

[0094] For the convenience of testing, all glass substrates were ultrasonically cleaned with ethanol and dried at 60 ° C before use. First, 8 parts of commercially available epoxy resin, 1 part of DDM and 90 parts of acetone were mixed under stirring conditions by mass, and then the mixture was sprayed onto a glass slide and pre-cured for 30 minutes at 60 ° C as a substrate. Then, the super hydrophobic antifreeze coating was sprayed on the substrate surface with a spray gun. Finally, it was cured for 8 hours at 60 ° C to obtain a coating sample. Among them, the sprayed air pressure was 30 psi.

[0095] 3. Test methods

[0096] Fourier Transform Infrared Spectroscopy (FTIR) Test

[0097] The samples were analyzed by transmission mode spectroscopy using a Nicolet 6700 Fourier transform infrared spectrometer from Thermo Fisher Scientific, USA. The scanning range of the spectrometer was 4000-400 cm -1 , resolution 4cm -1 , scan number 32. KBr pellet was used in transmission mode.

[0098] X-ray Photoelectron Spectroscopy (XPS) Test

[0099] The element types and composition of the samples were analyzed using an AXIS Ultra DLD X-ray photoelectron spectrometer from Kratos Analytical Instruments, UK, using a monochromatic Al Kα X-ray source (40 kV, 40 mA) at room temperature. All binding energies were calibrated to the C1 s hydrocarbon peak at 284.8 eV. All samples were dried in a vacuum oven at 65 °C for 24 hours before testing. The energy spectrum data and spectra of elements such as C, N, O, P, and Si were recorded.

[0100] Scanning electron microscopy (SEM) analysis

[0101] The surface morphology of all samples was observed using an Inspect F scanning electron microscope from FEI, USA. Test conditions: acceleration voltage 20 kV, samples were gold-sprayed before testing. The elemental spectrum was obtained using an energy dispersive X-ray spectroscopy (EDS) elemental composition analyzer installed on the scanning electron microscope.

[0102] Static contact angle test

[0103] Contact angle measurements were performed under ambient conditions using a Krüss DSA25 optical contact angle analyzer (Hamburg, Germany).

[0104] Thermogravimetric analysis (TGA)

[0105] The Q50 thermogravimetric analyzer from TA Instruments, USA, was used to test the mass change of the sample with temperature in a N2 atmosphere. Heating rate: 10°C / min; temperature range: 40-800°C.

[0106] Ice resistance test observation

[0107] The anti-icing properties of the material were tested using a homemade low-temperature test device. All experiments were conducted at a humidity of about 80±5% RH. The freezing process of the droplets was then recorded by a camera.

[0108] Roughness test

[0109] The surface morphology and roughness of the coatings were measured by laser confocal microscopy (LSM 700).

[0110] Verification Example 1

[0111] Verification Example 1 is carried out according to steps (1), (2) and (5) of "2. Preparation method" above, that is, the wind turbine blade powder obtained in step (2) is directly used as a raw material and mixed with ethanol to prepare the hydrophobic coating.

[0112] The grinding times in step (2) is 1 time, and finally a hydrophobic coating is prepared, and its coating sample is tested.

[0113] First, the effects of different pulverization methods on the hydrophobicity of the final prepared coatings were compared for wind turbine blade materials, as shown in Table 1:

[0114] Table 1 Effect of different grinding methods on hydrophobicity

[0115] Crushing method Processing time / min Average particle size / μm Water contact angle / ° Jaw Crusher 240 31.45 79.8 Planetary ball mill 150 31.12 80.1 Frozen ball mill 120 30.15 82.3 Verification Example 1 5 30.51 86.3

[0116] Table 1 shows the implementation scheme based on Example 1, on which only the disc-shaped solid phase mechanochemical reactor is replaced with other conventional pulverizing equipment, and the obtained wind turbine blade powders are all sieved through 500 mesh. It is obvious that under similar particle size conditions, the hydrophobic performance of Example 1 is significantly improved.

[0117] Verification of Examples 2 to 5

[0118] Verification Examples 2 to 5 are referenced to Verification Example 1, wherein the grinding times in step (2) are 2, 3, 5, and 10 times, respectively, and finally a hydrophobic coating is prepared and its coating samples are tested.

[0119] Secondly, the effects of different grinding times on the hydrophobicity of the final prepared coating were compared, as shown in Table 2:

[0120] Table 2 Effect of different grinding times on hydrophobicity

[0121] Grinding times / times Average particle size / μm Water contact angle / ° 0 1935 68.6 Verification Example 1 1 30.68 86.4 Verification Example 2 2 21.08 88.2 Verification Example 3 3 19.19 88.7 Verification Example 4 5 19.17 88.9 Verification Example 5 10 18.58 89.1

[0122] In Table 2, the number of grinding times is 0, which means that step (2) is not performed based on the implementation scheme of Example 1, that is, the wind turbine blade crushed material obtained in step (1) is used as the raw material to perform step (5). It is obvious that with the increase of the number of grinding times, the particle size of the wind turbine blade powder shows a decreasing trend, but the trend of increasing its hydrophobicity is not obvious. Based on comprehensive considerations, the number of grinding times is preferably 2 to 3 times.

[0123] Example 1

[0124] Example 1 is according to the above-mentioned "2. Preparation method", wherein the grinding times in step (2) is 1 time, and finally a super hydrophobic antifreeze coating is prepared, and its coating sample is tested.

[0125] Example 2

[0126] Example 2 is according to the above-mentioned "2. Preparation method", wherein the grinding times in step (2) is 2 times, and finally a super hydrophobic antifreeze coating is prepared, and its coating sample is tested.

[0127] Example 3

[0128] Example 3 is according to the above-mentioned "2. Preparation method", wherein the grinding times in step (2) is 3 times, and finally a super hydrophobic antifreeze coating is prepared, and its coating sample is tested.

[0129] Example 4

[0130] Example 4 is according to the above-mentioned "2. Preparation method", wherein the grinding times in step (2) is 5 times, and finally a super hydrophobic antifreeze coating is prepared, and its coating sample is tested.

[0131] Example 5

[0132] Example 5 is according to the above-mentioned "2. Preparation method", wherein the grinding times in step (2) is 10 times, and finally a super hydrophobic antifreeze coating is prepared, and its coating sample is tested.

[0133] Based on the coating sample obtained in Example 3, a paper was used for repeated rubbing, and its water contact angle was tested after the experiment. A 1N positive pressure was applied to the rubbing paper, and the number of rubbing cycles was 20, 60, 100, 140, 180, 220, 260, and 300. The effect of different rubbing times on the hydrophobic stability of the coating sample is shown in Table 3:

[0134] Table 3 Effect of different grinding times on hydrophobic stability

[0135] Friction times / times Water contact angle / ° 20 162.1 60 160.1 100 158.1 140 160.4 180 155.0 220 154.4 260 149.5 300 147.2

[0136] The coating samples obtained in Example 3 were immersed in 1 mol / L HCl solution for a specified time. After the experiment, the water contact angle was tested. The specified immersion time was 8, 16, 24, 32, 40, and 48 hours. The effects of different immersion times on the hydrophobicity of the coating samples are shown in Table 4:

[0137] Table 4 Effect of different immersion time in acid solution on the hydrophobicity of coating samples

[0138] Soaking time / hour Water contact angle / ° 8 161.0 16 162.3 24 158.4 32 157.2 40 159.3 48 156.4

[0139] Based on the coating sample obtained in Example 3, it was immersed in 1 mol / L NaCl solution for a specified time. After the experiment, its water contact angle was tested. The specified immersion time was 8, 16, 24, 32, 40, and 48 hours. The effect of different immersion times on the hydrophobicity of the coating samples is shown in Table 5:

[0140] Table 5 Effect of different immersion time in salt solution on the hydrophobicity of coating samples

[0141] Soaking time / hour Water contact angle / ° 8 161.1 16 158.3 24 158.5 32 158.4 40 156.8 48 152.6

[0142] Based on the coating sample obtained in Example 3, it was immersed in 1 mol / L NaOH solution for a specified time. After the experiment, its water contact angle was tested. The specified immersion time was 4, 8, 12, 16, 20, and 24 hours. The effect of different immersion times on the hydrophobicity of the coating samples is shown in Table 6:

[0143] Table 6 Effect of different immersion time in alkaline solution on the hydrophobicity of coating samples

[0144] Soaking time / hour Water contact angle / ° 4 158.4 8 155.3 12 153.3 16 150.1 20 145.5 24 132.6

[0145] Based on the coating sample obtained in Example 3, water flow impact was used, and after the experiment, its water contact angle was tested. Among them, the impact angle was 45°, the water flow speed was 10g / s, the water flow height was 15cm, and the impact time was 5 to 30 minutes. The effect of water flow impact time on the hydrophobicity of the coating sample is shown in Table 7:

[0146] Table 7 Effect of different water flow impact time on the hydrophobicity of coating samples

[0147] Impact time / minute Water contact angle / ° 5 160.1 10 157.1 15 159.7 20 157.2 25 158.2 30 156.2

[0148] Based on the coating sample obtained in Example 3, the antifreeze ability test was carried out in a refrigerator to observe its ice coverage, wherein the temperature was set at -15°C and the freezing time was 0 to 6 hours. The effect of freezing time on the dynamic antifreeze performance of the coating sample is shown in Table 8:

[0149] Table 8 Effect of different freezing time on dynamic antifreeze performance of coating samples

[0150] Freezing time / hour Ice coverage / % 0.5 0 1 0 2 15 3 28 4 49 5 65 6 79

[0151] Comparative Example 1

[0152] Comparative Example 1 is to mix 8 parts of commercially available epoxy resin, 1 part of DDM and 90 parts of acetone by weight under stirring, then spray the mixture onto a glass slide, and pre-cure it at 60°C for 30 minutes to serve as a coating comparison sample. The spraying air pressure is 30 psi.

[0153] Comparative Example 2

[0154] Comparative Example 2 is calculated by mass, 8 parts of commercially available epoxy resin, 1 part of DDM and 90 parts of acetone are mixed under stirring conditions, and then the mixture is sprayed on a glass slide and pre-cured for 30 minutes at a temperature of 60°C as a substrate. Then, 3 parts of 1H, 1H, 2H, 2H-perfluorodecyl acrylate are mixed with 95 parts of ethanol as a coating and sprayed on the surface of the substrate with a spray gun. Finally, it is cured at a temperature of 60°C for 8 hours to obtain a coating comparison sample. Among them, the sprayed air pressure is 30psi.

[0155] The water contact angle test was performed on the samples obtained from Example 3, Verification Example 3, Comparative Example 1, and Comparative Example 2. The hydrophobicity comparison of different hydrophobic coatings is shown in Table 9:

[0156] Table 9 Comparison of hydrophobicity of different hydrophobic coatings

[0157] Hydrophobic coating Water contact angle / ° Comparative Example 1 EP 92.4 Verification Example 3 EP / WGE 89.1 Comparative Example 2 EP / PFTDA 119.3 Example 3 EP / S@WGE@Kh 162.0

[0158] The samples obtained in Example 3 and Comparative Example 1 were tested for antifreeze performance, wherein the temperature was set at -15°C and the freezing time was 0.5 and 1 hour respectively. The dynamic antifreeze performance comparison of different hydrophobic coatings is shown in Table 10:

[0159] Table 10 Comparison of dynamic antifreeze performance of different hydrophobic coatings

[0160]

[0161] The coating samples obtained in Example 3 were contacted with milk, tea, coffee, orange juice and cola, respectively, and their contact angles were measured. The effects of different liquid environments on the hydrophobicity of the coating samples are shown in Table 11:

[0162] Table 11 Effect of different liquid environments on the hydrophobicity of coating samples

[0163] Contact with liquid Contact angle / ° milk 158.0 Tea 160.0 coffee 157.0 Orange juice 159.0 Cola 156.0

[0164] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a super-hydrophobic antifreeze coating using discarded wind turbine blades, characterized in that The main steps include: (1) After pretreatment including cleaning, the waste wind turbine blade materials are crushed into wind turbine blade fragments with an average particle size of no more than 3 cm; (2) adding the wind turbine blade fragments obtained in step (1) into a grinding disc-shaped solid phase force chemical reactor for grinding and pulverization, and collecting the wind turbine blade powder after the grinding is completed; wherein the process parameters of the grinding disc-shaped solid phase force chemical reactor are: grinding pressure of 4 to 6 MPa, the grinding disc surface temperature is controlled at 20 to 30° C. by passing a circulating cooling liquid, the grinding number is at least 1, and the grinding disc speed is 20 to 40 rpm; (3) modifying the wind turbine blade powder obtained in step (2) with a silane coupling agent containing a mercapto group to obtain a mercapto-functionalized modified wind turbine blade powder; (4) subjecting the thiol-functionalized modified wind turbine blade powder obtained in step (3) to a fluorinated acrylate through a thiol-ene click chemical reaction to generate a super-hydrophobic antifreeze composite powder; Wherein, the number of fluorine atoms in the fluorine-containing acrylate is at least 1 and the carbon chain length is 4 to 20; (5) According to the mass fraction, the super hydrophobic antifreeze composite powder obtained in step (4) is used as a raw material, and is mixed evenly with the following other raw materials to prepare a super hydrophobic antifreeze coating: 3-5 parts of super hydrophobic antifreeze composite powder, 90-95 parts of solvent.

2. The method according to claim 1, characterized in that: The mercapto-containing silane coupling agent in step (3) includes any one or more of KH590 and KH580.

3. The method according to claim 1, characterized in that: The wind turbine blade powder described in step (3) is modified by a silane coupling agent containing a mercapto group to obtain a mercapto-functionalized modified wind turbine blade powder, and the specific method is as follows: By weight, 1 to 2 parts of wind turbine blade powder are added to 90 to 99 parts of ethanol and 1 to 3 parts of deionized water, and the mixture is dispersed by stirring for 30 to 40 minutes. Then, 1 to 5 parts of a mercapto-containing silane coupling agent are added, and the mixture is stirred and reacted at a temperature of 90 to 100° C. for 8 to 16 hours. After the time is up, the mercapto-functionalized modified wind turbine blade powder is obtained by filtering, washing and drying.

4. The method according to claim 1, characterized in that: The fluorinated acrylate in step (4) includes 1H,1H,2H,2H-perfluorodecyl acrylate, trifluoroethyl acrylate, N-ethyl perfluorooctyl sulfonamidoethyl acrylate, 1,1,2,2-tetrahydroperfluorohexyl methacrylate, 1,1,2,2-tetrahydroperfluorodecyl methacrylate, 1,1,2,2-tetrahydroperfluorooctyl methacrylate, 1,1,2,2-tetrahydroperfluorododecyl methacrylate, 1,1,1,3,3,3-hexafluoroisopropyl acrylate, 3-(perfluoro-5-methyl)-1-nitropropene any one of 1H,1H,2H,2H-perfluorooctanol acrylate, 1,1,2,2-tetrahydroperfluorotetradecane acrylate, 2,2,3,3-tetrafluoropropyl methacrylate, 1H,1H-perfluoropropyl methacrylate, 2-(perfluorobutyl)ethyl acrylate, perfluoroalkylethyl methacrylate, perfluoroalkylethyl acrylate, nonafluorohexadecyl acrylate, (2H-perfluoropropyl)-2-acrylate, and (perfluorocyclohexyl) methacrylate.

5. The method according to claim 1, characterized in that: In step (4), the thiol-functionalized modified wind turbine blade powder and the fluorinated acrylate are reacted by a thiol-ene click chemical reaction to generate a super-hydrophobic antifreeze composite powder, which is to fully dilute and disperse the thiol-functionalized modified wind turbine blade powder into a mixed solution B with a mass concentration of 1 to 10wt%, dilute the fluorinated acrylate to a fluorinated acrylate solution with a mass concentration of 2 to 25wt%, add the fluorinated acrylate solution to the mixed solution B under stirring, then add an initiator, stir and react at a temperature of 60 to 80°C for 9 to 12 hours, and after the time is up, filter, wash and dry to obtain the super-hydrophobic antifreeze composite powder.

6. The method according to claim 5, characterized in that: The initiator comprises any one of azobisisobutyronitrile, triethylamine, 2-methyl-1-(4-methylthiophenyl)-2-morpholinyl-1-propanone and 4-dimethylaminopyridine; the added amount of the initiator is 1-20% of the mass of the mercapto functionalized modified wind turbine blade powder.

7. The method according to claim 1, characterized in that: The solvent in step (5) includes any one or more of anhydrous ethanol, n-hexane, cyclohexane, dichloromethane, n-heptane, n-octane, acetone, benzene, toluene, and ethyl acetate.

8. The method according to claim 1, characterized in that: The raw materials include: 1 to 10 parts of filler, 1 to 10 parts of additives.

9. The method according to claim 1, characterized in that: The grinding times in step (2) is 2 to 3 times.

10. The super hydrophobic antifreeze coating prepared by the method for preparing super hydrophobic antifreeze coating using discarded wind turbine blades as claimed in claim 1.

Citation Information

Patent Citations

  • Mechanico-chemical reactor

    CN1130545A

  • An industrial millstone-shaped solid-phase mechanochemical reactor

    CN114534660B

  • Multifunctional super-amphiphobic fabric and preparation method thereof and application thereof

    CN109610161A

  • Super-hydrophobic and super-oleophobic epoxy resin coating and preparation method thereof

    CN112831241A

  • Anti-icing hydrophobic coating as well as preparation method and application thereof

    CN116836593A

Cited By

  • Method for high-value recycling of unsaturated polyester glass fiber reinforced plastic waste material

    CN120173388A